COVID-19 and death of older adults in the Northeast region of Brazil: a survival analysis/ COVID-19 y muerte de ancianos en la región Nordeste de Brasil: un análisis de supervivencia/ COVID-19 e óbito de pessoas idosas na região Nordeste do Brasil: uma análise da sobrevivência - Nascimento, Marcelo de Maio (Journal Health NPEPS, 2021)
Objective: to analyze survival and factors associated with increased risk of death for older adults diagnosed with COVID-19, living in the Northeast region of Brazil. Method: retrospective observational study developed with secondary data provided by the Brazilian Ministry of Health, between June 14 and December 26, 2020. The Kaplan-Meyer method, the time-dependent cox regression model was used, including covariates (age, sex, skin color, comorbidities, admission to the ICU, ventilatory support). Results: out of 9,306 individuals analyzed, 55.9% died and 44.1% survived. The highest risk of death was observed for those aged 80-89 (HR=1.95), brown-skinned (HR=1.99), with immunodeficiency (HR=1.259) or kidney disease (HR=1.147), admitted to the ICU (HR=1,795) and in use of ventilatory support (HR=1606). Conclusion: among older adults residing in the Northeast region of Brazil, there was a higher risk of death from COVID-19 for octogenarians, brown-skinned, with comorbidities, hospitalization in the ICU, followed by the use of ventilatory support. The creation of health prevention strategies that identify older adults with these profiles is suggested to prevent deaths in future pandemic situations.